An??lise e discuss??o da proposta formativa do curso de turismo - Santos, Jaqueline Silva dos (2013)
It is philosophical reflection on the educational proposal of Tourism Course, in the context of the discussion of the meaning of vocational training college. Searching answer the question of how to ensure a humanistic education for the professional tourism. The hypothesis that guides the goals of this work is that the professional training of Tourism has a predominantly technical and pragmatic enough to prepare you adequately for productive praxis, social and cultural. To address this hypothesis to study after explaining the philosophical underpinnings that support training in tourism, which raises the theoretical approaches that guide the tourism studies, how these approaches impact training in tourism, as these approaches are realized in Public Policy focused for Higher Education in Tourism. The categories which express the historical practices, represented by Labour, the Sociability and Culture, which guided this study are based on the thought that Ant??nio Joaquim Severino discusses higher education and human development. As a result proposes bases for the debate with a new degree in Tourism.